The experiences of pupils with SEN and their parents at the stage of pre-transition from primary to post-primary school. Issue 1 (2nd January 2016) - Scanlon, Geraldine; Barnes-Holmes, Yvonne; McEnteggart, Ciara; Desmond, Deirdre; Vahey, Nigel
Abstract: The experiences of pupils with Special Educational Needs (SEN) and their parents at pre-transition from primary to post-primary school have received little attention in the literature. The current study investigated these experiences using a mixed methods approach within the Irish educational system. Thirty-two pupils with SEN and 42 parents of pupils with SEN participated in focus groups, and also completed a questionnaire which qualitatively complemented the parental focus groups. Emergent themes for pupils included: things I will miss; fitting in and performing as well as others; laying the groundwork: getting to know new people; and experiencing and talking about 'going to the new school'. Emergent themes for parents included: losing ground?; information is critical: 'I'm not asking for the moon, but a bit more information'; I'd like help but I don't want to make trouble for my child; and challenge and support. Critical issues emerging from the data concerning pre-transition experiences for both pupils and parents are discussed.